Human Papillomavirus Species-Specific Interaction with the Basement Membrane-Resident Non-Heparan Sulfate Receptor - Kathleen F. Richards; Santanu Mukherjee; Malgorzata Bienkowska-Haba; Jia Pang; Martin Sapp (Viruses, 2014)
Using a cell culture model where virus is bound to the extracellular matrix (ECM) prior to cell surface binding, we determined that human papillomavirus type 16 (HPV16) utilizes ECM resident laminin (LN) 332 as an attachment receptor for infectious entry. In presence of LN332, soluble heparin can function as ligand activator rather than competitive inhibitor of HPV16 infection. We also show that the ability to use LN332 binding as a productive attachment step for infectious entry is not conserved amongst HPV types. In the alpha genus, species 9 members (HPV16) attach to ECM via LN332, while members of species 7 (HPV18) are completely inhibited by heparin pre-incubation due to an inability to use LN332. Since HPV species 7 and 9 are preferentially associated with adenocarcinoma and squamous cell carcinoma of the cervix, respectively, our data provide first evidence that pre-entry events may contribute to the anatomical-site preference of HPV species.